Effect of sintering temperature on microstructure and strength distribution of alumina ceramic springs - Nohut, S.; Perottoni, C.; Lu, Chunsheng; Barbieri, R.; Zorzi, J. (Maney Publishing (W.S. Maney & Son Ltd), 2013)
Ceramic coil springs are one of the most widely used components in mechanical systems under harsh chemical conditions and high temperatures. In real applications of ceramic coil springs, knowing the effect of sintering temperature on their microstructure and strength distribution plays a crucial role. In this paper, the microstructure and strength distribution of alumina coil springs sintered at 1550, 1600 and 1650°C are investigated. Strength data of alumina coil springs are fitted by a Weibull distribution and according to the coefficient of determination, the deviation from the Weibull distribution can be determined. It is shown that the Weibull distribution best fits the strength data of alumina coil springs sintered at 1600°C. The probable reasons for deviation from the Weibull distribution are discussed in terms of grain size, porosity, and R curve behaviour.